Analysis of Religious Character Values and Global Diversity in Elementary School Students in Morning Habituation Activities - muna, muflihatun nailil; Saputro, Bagus Ardi; Suratmi, Suratmi; Reffiane, Fine (DIDAKTIKA, 2024)
Character education at the elementary school level in Indonesia is an important aspect in the formation of students' personalities. This study aims to analyze how morning habituation activities in elementary schools contribute to the cultivation of religious character values and global diversity which are part of the Pancasila Student Profile. This research was conducted in elementary schools in Semarang using descriptive qualitative research methods. Data collection was carried out through observation, interviews with pamong teachers, and documentation of activities. The results of the study show that morning habituation activities such as flag ceremonies, joint prayers, morning apples, and introduction to regional culture and languages play a role in the formation of students' religious character and global diversity. This activity helps students understand, appreciate, and apply religious values and appreciate cultural diversity.Â Activities such as 5S (Greeting, Smile, Greeting, Politeness, and Manners), joint prayers, and introduction to regional culture function as a means of supporting character education in accordance with the Pancasila Student Profile. The conclusion of this study is that morning habits in elementary school play an important role in the formation of religious attitudes and global diversity of students, so as to create an inclusive and tolerant school environment. Morning habits play a role in strengthening religious values and increasing students' understanding of cultural diversity and tolerance, supporting the formation of a young generation with noble character and a good attitude of tolerance towards differences.